Morphological Analysis of an Ecolinguistics Text - Kadek Putri Yuniari; I Made Juliarta (Universitas Bali Dwipa, 2026)
Morphology is a central field in linguistics that examines the internal structure of words and the processes by which they are formed. A key concept in morphological studies is the morpheme, defined as the smallestmeaningful unit of language. This study aims to analyze the types and functions of morphemes found in an academic ecolinguistics text in order to illustrate how morphological processes operate in written discourse. The data for this study were obtained from selected lexical items and sentences taken from a subchapter of ArranStibbe’s Ecolinguistics. A qualitative descriptive method was employed to identify and classify free morphemes,bound morphemes, derivational morphemes, inflectional morphemes, compound words, and word classes. The analysis was conducted by segmenting words into their morphemic components and examining their grammatical functions within context. The findings indicate that derivational morphemes, particularly those forming abstract nouns and technical terms, occur frequently in the text, reflecting the academic nature of ecolinguistics discourse. Inflectional morphemes mainly serve grammatical functions such as tense and number, while compound words contribute to the expression of interdisciplinary concepts. This study highlights the importance of morpheme analysis in understanding word formation and meaning construction in academic texts, especially in the field of linguistics.